(untitled) (Agora for Physical Education and Sport, 2021)
This article aims to account for the existing relationships between academic culture and the pedagogical practice of teachers in Physical Education training for the recognition of the existing conditions in the knowledge society. This is a qualitative research supported by the multiple case study. For the collection of information, the following techniques were used: semi-structured interviews, participant observation, and audiences. Among the results, there is a pedagogical practice subject to the logic of schools that, justified in the academic culture of the knowledge society, reduces the autonomy of teachers in training.